Optimization of the Pretreatment of the Mixture of Cassava Peelings and Pineapple Fibers Using the Organosolv Process for the Bioethanol Production - Atchana, Jeanne; Djonga, Paul Nestor Djomou; Ngbara, Judith; Talla, André; Nkeng, George Elambo; Seronfe, Doumbia Awa (Scientific Research, New Technologies and Applications Vol. 2, 2024)
The biggest concern of households in our different municipalities remains access to stable, quality energy, respect for the environment, and above all a lower cost. The increase in oil prices and greenhouse gas emissions have led to the search for substitutes for fossil fuels. In Cameroon, the abundance of lignocellulosic resources is inherent to agricultural activity. Production of bioethanol remains a challenge given the crystallinity of cellulose and the presence of the complex. The pretreatment aimed to solubilize the lignin fraction and to make cellulose more accessible to the hydrolytic enzymes was done using the organosolv process. Mathematical modeling was performed to point out the effect of the temperature on the kinetics of the release of the reducing sugars during the pretreatment. The aim of the study is to optimize the pretreatment of the mixture of cassava peelings and pineapple fibers for bioethanol production. Two mathematical models such as SAEMAN's model and Response surface methodology were used. The first shows that the kinetic parameters of the hydrolysis of the cellulose and reducing sugar are: 0.05089 min-1, 5358.1461 J.mol-1, 1383.03691 min-1, 51577.6100 J.mol-1 respectively. In order to better control this pre-treatment step, modeling by the second model was used. Temperature is the factor having the most positive influence whereas, ethanol concentration is not an essential factor. The model equation reveals that this positive contribution is significant on the Response surface and not significant on the cellulose. To release the maximum, an organosolv pre-treatment of this substrate should be carried out at 209.08°C for 47.60 min with an ethanol-water ratio of 24.02%. Organosolv pre-treatment is an effective process for the delignification of the lignocellulosic structure. To improve this work, it would be wise to carry out a technical-economic analysis of the process and make an energy assessment of the installation.